Induction of neuronal differentiation in PC12 cells by B-cell stimulatory factor 2/interleukin 6. - Satoh, T (1988)
B-cell stimulatory factor 2 (BSF-2) is a lymphokine which induces the final maturation of B cells. BSF-2 acts on a variety of cells other than B cells, and moreover, expression of BSF-2 mRNA is detected in interleukin-1 beta-stimulated glioblastoma and astrocytoma cell lines. Here, we studied the function of BSF-2 on pheochromocytoma PC12 cells, a model system for induction of neuronal differentiation. PC12 cells possess specific receptors for BSF-2. The BSF-2-stimulated PC12 cells expressed the c-fos proto-oncogene transiently, and they began to change morphologically to neurite-extending cells after several days. The number of voltage-dependent Na+ channels was also increased.